Pseudomonas fluorescens MFE01 delivers a putative type VI secretion amidase that confers biocontrol against the soft‐rot pathogen Pectobacterium atrosepticum - Yvann Bourigault; Charly A. Dupont; Jonas B. Desjardins; Thierry Doan; Mathilde Bouteiller; Hugo Le Guenno; Sylvie Chevalier; Corinne Barbey; Xavier Latour; Eric Cascales; Annabelle Merieau (Environmental Microbiology, 2023)
The type VI secretion system (T6SS) is a contractile nanomachine widespread in Gram‐negative bacteria. The T6SS injects effectors into target cells including eukaryotic hosts and competitor microbial cells and thus participates in pathogenesis and intermicrobial competition. Pseudomonas fluorescens MFE01 possesses a single T6SS gene cluster that confers biocontrol properties by protecting potato tubers against the phytopathogen Pectobacterium atrosepticum (Pca). Here, we demonstrate that a functional T6SS is essential to protect potato tuber by reducing the pectobacteria population. Fluorescence microscopy experiments showed that MFE01 displays an aggressive behaviour with an offensive T6SS characterized by continuous and intense T6SS firing activity. Interestingly, we observed that T6SS firing is correlated with rounding of Pectobacterium cells, suggesting delivery of a potent cell wall targeting effector. Mutagenesis coupled with functional assays then revealed that a putative T6SS secreted amidase, Tae3 Pf , is mainly responsible for MFE01 toxicity towards Pca. Further studies finally demonstrated that Tae3 Pf is toxic when produced in the periplasm, and that its toxicity is counteracted by the Tai3 Pf inner membrane immunity protein.